2014
DOI: 10.2110/palo.2013.100
|View full text |Cite
|
Sign up to set email alerts
|

Mollusk Successions of Holocene Shallow-Lake Deposits From the Southeastern Pampa Plain, Argentina

Abstract: We analyzed variations in taxonomic composition, abundance, and preservation of freshwater mollusks during the mid-to late Holocene in three shallow lakes of the southeastern Pampa plain. Mollusks were obtained from core samples (110-140 cm long) from the deepest part of the lakes, and sampled at 1 cm intervals. Six species were identified: Heleobia australis, Heleobia parchappii, Biomphalaria peregrina, Uncancylus concentricus, Succinea meridionalis, and Antillorbis nordestensis. Assemblages were dominated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…In fact, taphonomic changes agree well with environmental changes (see De Francesco et al 2013). For example, surface alteration was lower in levels where brackish to saline water conditions were inferred.…”
Section: Mollusk Preservationsupporting
confidence: 67%
See 1 more Smart Citation
“…In fact, taphonomic changes agree well with environmental changes (see De Francesco et al 2013). For example, surface alteration was lower in levels where brackish to saline water conditions were inferred.…”
Section: Mollusk Preservationsupporting
confidence: 67%
“…Previous studies of these records indicated the occurrence of wide paleoenvironmental changes, particularly related to fluctuations in salinity, water depth, and nutrient status (Stutz et al 2010(Stutz et al , 2012De Francesco et al 2013;Hassan 2013). These environmental changes may have affected diatom and mollusk preservation in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Both the modern and Quaternary mollusk communities in the province of Buenos Aires are represented by few families and genera (Tietze and De Francesco 2012;De Francesco et al 2013;Steffan et al 2014). Between the few species found, representatives of Helobia are most abundant.…”
Section: Quaternary Malacofaunamentioning
confidence: 99%
“…Heleobia parchappii is the dominant species in the modern freshwater environments of the Pampean region (Tietze et al 2011) and shows relative abundances that reach 90%-100% of mollusk faunas in Quaternary sediments (De Francesco and Zárate 1999;De Francesco et al 2013). This is an opportunistic species with high reproductive rates (Tietze et al 2011) living in freshwater environments such as rivers, creeks and lakes, although it can tolerate higher salinities (Tietze and De Francesco 2010).…”
Section: Quaternary Malacofaunamentioning
confidence: 99%
See 1 more Smart Citation